Unicity theorems with truncated multiplicities of meromorphic mappings in several complex variables for few fixed targets - Pham, Hoang Ha; Si, Duc Quang (Ukrains’kyi Matematychnyi Zhurnal, 2019)
The purpose of our paper is twofold. Our first aim is to prove a uniqueness theorem for meromorphic mappings of $C^n$ into$P^N(C)$ sharing $2N + 2$ hyperplanes in the general position with truncated multiplicities, where all common zeros withmultiplicities more than a certain number do not need to be counted. Second, we consider the case of mappings sharingless than $2N + 2$ hyperplanes. These results are improvements of some recent results.